A Longitudinal Comparison of Pharmacy Documentation Platforms Using the Technology Acceptance Model: Experiences With Opioid Risk Screening. (February 2023) - Frenzel, Oliver C.; Strand, Mark; Welsh, Allison; Eukel, Heidi; Skoy, Elizabeth; Steig, Jayme; Werremeyer, Amy
Background: Pharmacy practice continues to expand in scope, and technology platforms to assist with meeting the standards for documentation of billable services are needed. The ONE Program (Opioid and Naloxone Education) is an initiative centered on the community pharmacy focused on opioid risk screening for patients receiving opioid prescriptions.Objective: Opioid risk screening results and pharmacist interventions were documented using first REDCap and later the DocStation platforms. This study compared pharmacy staff experience with these 2 platforms.Methods: A survey using the Technology Acceptance Model (TAM) was designed to compare usability, ease of use, social influence, and facilitating conditions.Results: Analyses using descriptive statistics and open-ended responses showed similar results for each platform; however, pharmacy staff indicated that REDCap required less time when entering information, whereas the DocStation platform offered elevated pharmacy practice service opportunities, management support, and available informational technology support services.Conclusion: Health care technology continues to advance in meeting the needs of expanded service provision through pharmacy. This longitudinal study shows the value of the TAM framework in identifying efficiencies and deficiencies of health care technology systems.